The Effect of Argumentation Skills and Problem Based Learning on Science Literacy of High School Students - Handayani, Mawaddah; Khairuna, Khairuna (Jurnal Pendidikan MIPA, 2022)
rgumentation is one of the methods used to strengthen students' scientific concepts, especially in biology learning. This quantitative study aims to determine the effect of argumentation skills on students' scientific literacy and also to find out the improvement of students' scientific literacy by using argumentation skills of class X IPA-1 MAS CIPTA students of Simpang Dolok village. The population in this study involved the entire class X IPA-1 MAS CIPTA Simpang Dolok village, the sampling in this study used a simple random sampling technique without a control class. The instruments in this study were Essay test questions with scoring that adapted from TAP (Toulmin's Argumentation Petteren) for argumentation skills and essay tests for scientific literacy. The data was collected using a tabular sheet obtained from the argumentation Skill scores and the pretest and posttest scores for scientific literacy. As well as document documentation and photos. The data analysis technique uses the calculation of the N-gain score of scientific literacy due to the influence of Argumentation Skills, while the hypothesis testing uses a simple linear regression test and a paired simple t-test. The results of this study indicate that there is a positive and significant linear effect between argumentation skills on students' scientific literacy and a significant increase in students' scientific literacy using argumentation skills. Keywords: scientific literacy, problem based learning, argumentation skill. DOI: http://dx.doi.org/10.23960/jpmipa/v23i3.pp1286-1295